EXPRESSIVE PATTERN DRAWING IN GROUP COUNSELING FOR VOCATIONAL STUDENTS’ EMOTIONAL REGULATION IMPROVEMENT - Ali Murtadho; Asieline Wahyu Tri Ardyanti; Budi Purwoko; Evi Winingsih (EDUCATIONE, 2026)
Emotional regulation is an essential aspect of students’ development, particularly for vocational high school students who are in a critical period of emotional and social adjustment. However, many students still experience difficulties in managing their emotions adaptively, which may negatively affect their learning process and social interactions. Therefore, appropriate and developmentally relevant interventions are needed. This study aimed to examine the effect of group counseling based on expressive pattern drawing on students’ emotional regulation abilities. This study employed a quantitative approach using a pre-experimental One Group Pretest–Posttest Design. The respondents consisted of eleventh-grade students at SMK Sejahtera Surabaya who demonstrated low emotional regulation abilities and were selected through purposive sampling. Data were collected using an emotional regulation questionnaire with a four-point Likert scale, which had been tested for validity and reliability, yielding a Cronbach’s Alpha coefficient of 0.832. The intervention was conducted through group counseling sessions utilizing expressive pattern drawing techniques over five sessions. Data analysis was performed using the Wilcoxon Signed Rank Test with the assistance of SPSS version 25. The results indicated an improvement in emotional regulation abilities among all participants after the intervention. The Wilcoxon test revealed an Asymp. Sig. (2-tailed) value of 0.027 (< 0.05), indicating that group counseling based on expressive pattern drawing had a significant effect on improving emotional regulation abilities among vocational high school students.